ANALYSIS OF THE PROOF STRENGHT OF A DEED MADE BEFORE A NOTARY AS AN AUTHENTIC DEED IN CIVIL ACTION - Zaini, Zulfi Diane; Amanah, Safitta (Universitas Labuhanbatu, 2025)
A Notarial Deed is an Authentic Deed made by or before a Notary in accordance with the form and procedures stipulated in this Law. Making an Authentic Deed is required by statutory regulations in order to create certainty, guardianship and legal protection. The method used is a normative juridical approach and an empirical approach. The legal power of a Notarial Deed as Authentic Evidence in a Civil Lawsuit is perfect and binding, so it does not need to be made or supplemented with other evidence, the Deed remains in existence. What is canceled is the contents of the Deed (the legal relationship). Responsibility of the Notary for the Deed Made as Authentic Evidence in Civil Lawsuits, a Notary must be morally responsible for the Deed he makes because he is entrusted with compiling and formulating the wishes of the parties in the DeedKeywords: Authentic deed; Civil Law; Notary